Moisture-permeable waterproof laminated fabric, method for producing same, and garment using same
By waterproofing the nanofiber nonwoven fabric layer in the moisture-permeable waterproof layer and partially bonding it to the surface grey fabric layer, the problem of reducing the breathability and moisture permeability of the existing moisture-permeable waterproof materials when wet during wear is solved, and the problem of reducing the breathability and moisture permeability of existing moisture-permeable waterproof materials is achieved. Continuous breathability and moisture permeability under rain and sweat conditions ensure a comfortable environment in the clothes.
Patent Information
- Application Number
- CN202380043291.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-27
- Filing Date
- 2023-06-21
- Publication Date
- 2025-01-10
AI Technical Summary
The existing moisture-permeable waterproof materials cannot continuously exert breathability and moisture permeability when worn due to rain and sweat, resulting in a sultry and degradation of performance.
In the moisture-permeable waterproof layer, at least one side of the nanofiber nonwoven fabric layer is waterproofed and partially bonded to the surface grey fabric layer by an adhesive to form a waterproof layer to prevent rainwater and sweat from penetration.
It achieves continuous breathability and moisture permeability under dry and medium rain and sweat conditions, prevents the feeling of stuffy heat and performance degradation, and maintains a comfortable interior environment in the clothes.
Smart Images

Figure CN119300973A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a moisture-permeable waterproof laminated fabric having high moisture permeability and waterproofness, a method for producing the same, and clothing using the same. Background Art
[0002] In the past, there have been many proposals for breathable waterproof materials, mainly using porous materials (polytetrafluoroethylene: PTFE) formed by extrusion stretching technology, porous materials (polyurethane: PU) formed by wet coagulation, and non-porous materials (PU) formed by dry coagulation. These materials show high values in water pressure resistance and moisture permeability, but have not yet eliminated the feeling of stuffiness when worn. In addition, the non-porous film formed by the dry coagulation method has a hydrophilic nature. If it is wet due to sweating or rain, not only will the performance decline, but the quality will also decline due to the swelling of the film.
[0003] In recent years, a new type of moisture permeable film formed by a method other than the above method has been proposed. Specifically, a scheme of laminating nanofibers spun by electrostatic spinning has been proposed (Patent Documents 1 and 2). In addition, in the previous moisture permeable film, from the viewpoint of preventing oil pollution and the purpose of preventing the decrease in water pressure resistance caused by washing, a material in which a hydrophobic raw material is mixed in a polyurethane film has also been proposed (Patent Document 3). From the same viewpoint, in the nanofiber moisture permeable film, a process of implementing hydrophobic processing on nanofibers has also been proposed (Patent Document 4).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2007-136970
[0007] Patent Document 2: Japanese Patent Application Publication No. 2008-213391
[0008] Patent Document 3: Japanese Patent Application Publication No. 2010-255132
[0009] Patent Document 4: Japanese Patent Application Publication No. 2010-030289 Summary of the invention
[0010] Problems to be solved by the invention
[0011] However, although the above-mentioned prior art improves durability, there is still a problem that the moisture-permeable film itself becomes wetted by rainwater and sweat during wearing, and the breathability and moisture permeability of the moisture-permeable film cannot be exerted.
[0012] In order to solve the above-mentioned conventional problems, the present invention provides a moisture-permeable waterproof laminated fabric, a method for producing the same, and clothing that can continuously exhibit the air permeability and moisture permeability of a moisture-permeable film not only in a dry state but also in rain and sweat while being worn.
[0013] Means of solving problems
[0014] The moisture-permeable waterproof layer laminated fabric of the present invention is characterized in that it is a moisture-permeable waterproof layer laminated fabric having a nanofiber nonwoven fabric layer laminated on one side of a surface grey fabric layer, wherein at least one side of the nanofiber nonwoven fabric layer is a waterproof layer, and the surface grey fabric layer and the nanofiber nonwoven fabric layer are partially bonded by an adhesive.
[0015] The method for manufacturing a moisture-permeable waterproof layer laminated fabric of the present invention is a method for manufacturing a moisture-permeable waterproof layer laminated fabric in which a nanofiber nonwoven fabric layer is laminated on one side of a surface grey fabric layer, and is characterized in that a waterproof agent is applied to at least one side of the nanofiber nonwoven fabric layer and fixed to form a waterproof layer, and the nanofiber nonwoven fabric layer and the surface grey fabric layer are partially bonded using an adhesive.
[0016] The clothing of the present invention is characterized by using the above-mentioned moisture-permeable waterproof laminated fabric.
[0017] Effects of the Invention
[0018] In the moisture-permeable waterproof laminated fabric and clothing of the present invention, a nanofiber nonwoven fabric layer is laminated on one side of the surface grey fabric layer, at least one side of the nanofiber nonwoven fabric layer is a waterproof layer, and the surface grey fabric layer and the nanofiber nonwoven fabric layer are partially bonded by an adhesive, so that the breathability and moisture permeability of the moisture-permeable film can be continuously exerted not only in a dry state, but also under rain and sweat during wearing. That is, rainwater from the external air side of the moisture-permeable waterproof laminated fabric is prevented by the waterproof layer on the surface of the nanofiber nonwoven fabric, and sweat (humid sweat: gas) from the body side is diffused to the external air side through the gaps between the yarns of the surface grey fabric layer, the gaps in the woven structure, or the gaps in the nanofiber nonwoven fabric layer. Therefore, even under the action of rain and sweat during wearing, the breathability and moisture permeability of the nanofiber nonwoven fabric (moisture-permeable film) can be continuously exerted. As a result, the decrease in moisture permeability and water pressure resistance during wearing can be prevented, there is no stuffiness, and a comfortable inner environment of the clothes can be maintained. Furthermore, the method for producing a moisture-permeable waterproof laminated fabric of the present invention can efficiently and rationally produce the moisture-permeable waterproof laminated fabric. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a schematic cross-sectional view of a moisture-permeable waterproof laminated fabric having a two-layer structure according to one embodiment of the present invention.
[0020] Figure 2This is a schematic cross-sectional view of a moisture-permeable waterproof laminate fabric having a 2.5-layer structure according to one embodiment of the present invention.
[0021] Figure 3 This is a schematic cross-sectional view of a moisture-permeable waterproof laminated fabric having a three-layer structure according to one embodiment of the present invention.
[0022] Figure 4A -E is a schematic cross-sectional process diagram showing a method for producing a moisture-permeable waterproof laminated fabric having a three-layer structure according to one embodiment of the present invention.
[0023] Figure 5 This is a schematic cross-sectional view showing the bonding state of a nanofiber nonwoven fabric layer and a surface fabric layer according to one embodiment of the present invention.
[0024] Figure 6 This is a plan view photograph (SEM, magnification 10000 times) of a nanofiber nonwoven fabric according to one embodiment of the present invention.
[0025] Figure 7 This is a plan view photograph (SEM, 2000-fold magnification) of a nanofiber nonwoven fabric according to one embodiment of the present invention.
[0026] Fig. 8A 1 is a schematic development diagram showing a moisture permeability measuring device (original method) used in an example of the present invention. Figure 8B It is an assembled stereogram of the device. DETAILED DESCRIPTION
[0027] In the present invention, a nanofiber nonwoven fabric layer is laminated on one side of the surface grey fabric layer, at least one side of the nanofiber nonwoven fabric layer is a waterproof layer (waterproof surface), and the surface grey fabric layer and the nanofiber nonwoven fabric layer are partially bonded by an adhesive. The surface grey fabric layer refers to the grey fabric layer located on the outside when clothes are made in the state of laminated cloth. That is, it refers to the grey fabric layer that will be directly exposed to rain when worn on rainy days. In addition, the surface grey fabric layer can also be waterproofed, but it does not need to be water-resistant or waterproof. If the surface grey fabric layer is waterproofed, a small amount of rainwater can be repelled, but if it rains for a long time, rainwater will penetrate into the grey fabric. By giving a moisture-permeable waterproof layer to the inner side (skin side) of the surface grey fabric layer, rainwater that penetrates from the surface grey fabric layer can be prevented from entering the clothes. However, in the case where the moisture-permeable waterproof membrane is a non-porous membrane, since the membrane has the property of absorbing water, the rainwater that penetrates from the surface grey fabric layer is absorbed by the moisture-permeable waterproof membrane and enters the clothes, wetting the inner clothes and skin, causing the body temperature to drop. Therefore, by providing a waterproof processing layer on at least one side of the moisture-permeable waterproof film, water can be prevented from seeping into the clothes even when the surface grey fabric layer is wet. In addition, it is more preferred to apply a waterproof processing layer to the surface grey fabric layer side of the nanofiber nonwoven fabric. Thus, it is possible to more effectively prevent rainwater that penetrates from the surface grey fabric layer from being absorbed in the moisture-permeable waterproof film. In this specification, "at least one side" means any one of the surface, the back, and both sides.
[0028] In the waterproof processing layer applied to the nanofiber nonwoven fabric layer, the entire surface of the surface to be processed can be a waterproof surface, or it can be a partially waterproof surface. The entire surface is a waterproof surface, which means that in the waterproof processing layer applied to the nanofiber nonwoven fabric layer, 100% of the surface area of the nanofiber constituting the surface to be processed is waterproofed. The partially waterproof surface means that in the waterproof processing layer applied to the nanofiber nonwoven fabric layer, a part of the surface area of the nanofiber constituting the surface to be processed is waterproofed. Even if the entire surface is a waterproof surface, there are gaps between fibers in the thickness direction of the nanofiber nonwoven fabric layer, and the air permeability is good. Sweat (humid sweat: gas) from the body side is dissipated to the outside air side through the gaps between the yarns of the surface grey fabric layer, the gaps in the woven structure, or the gaps in the nanofiber nonwoven fabric layer. In addition, since at least one side of the nanofiber nonwoven fabric is a waterproof layer, rainwater from the outside air side is blocked by the waterproof layer on the surface of the nanofiber nonwoven fabric, and there is no stuffiness during and when wearing it. Even if it rains or sweats, the breathability and moisture permeability of the moisture permeable film can continue to be exerted. In this specification, the nanofiber nonwoven fabric with a waterproof layer is also referred to as a "moisture permeable film" or a "nano film".
[0029] The thickness of the waterproof layer is preferably 10 to 100% of the thickness of the nanofiber nonwoven fabric layer, more preferably 20 to 70%, and further preferably 30 to 50%. In this way, the waterproof layer can not only fully suppress the functional decline of the nanofiber nonwoven fabric when wet, but also discharge the retained moisture from the non-waterproof surface to the outside of the nanofiber nonwoven fabric layer.
[0030] When the fiber surface area of the nanofiber nonwoven fabric layer is set to 100%, the area ratio of the waterproof layer (waterproof surface) is preferably 10 to 100% by area ratio, more preferably 20 to 95% of the partial waterproof surface by area ratio, and further preferably 30 to 90% of the partial waterproof surface. In this way, the waterproofing agent will not clog the pores of the nanofiber nonwoven fabric (moisture permeable membrane) and can prevent water from entering. Here, the surface of the nanofiber nonwoven fabric layer refers to the nanofiber nonwoven fabric surface that has been waterproofed.
[0031] In the case of 100% waterproofing by area ratio, the waterproofing surface of the nanofiber nonwoven fabric layer constituting the nanofiber nonwoven fabric can be completely covered with a waterproofing agent. Therefore, when the grey fabric is wet, the nanofibers will not absorb and retain water, and the decline in functionality can be suppressed. In addition, since the detergent residue caused by washing can be suppressed, the decline in water pressure resistance caused by washing can also be suppressed.
[0032] In the case of 30-90% waterproofing treatment in terms of area ratio, 30-90% of the surface area of the waterproofing treatment surface of the nanofiber nonwoven fabric layer constituting the nanofiber nonwoven fabric can be covered with a waterproofing agent. If it is partially waterproof, the number of nanofibers whose fiber diameters of the nanofiber nonwoven fabric change due to the attachment of the waterproofing agent is reduced, so the gaps in the nanofiber nonwoven fabric will not be blocked, and the air permeability and moisture permeability when dry can be maintained at a high level. When the grey cloth is wet, it is possible to inhibit the nanofibers from absorbing and retaining water, inhibit the decline in functionality, and further inhibit the detergent residue caused by washing, so it is also possible to inhibit the decline in water pressure resistance caused by washing. The water-retained moisture can be discharged from the non-waterproof part to the outside of the nanofiber nonwoven fabric layer. Here, the area ratio refers to the ratio of the area of the waterproofing agent attached to the surface of the nanofiber nonwoven fabric when the sum of the surface areas of the nanofibers constituting the surface of the nanofiber nonwoven fabric is set to 100. In addition, the surface layer of the nanofiber nonwoven fabric refers to the layer on the side of the surface to which the waterproofing treatment is applied.
[0033] The moisture-permeable waterproof laminated fabric of the present invention may be a two-layer structure in which a nanofiber nonwoven fabric is laminated on one side of a surface fabric, a 2.5-layer structure in which a resin layer is laminated on one side of the nanofiber nonwoven fabric, or a three-layer structure in which a backside fabric is laminated on one side of the nanofiber nonwoven fabric and the nanofiber nonwoven fabric and the backside fabric are partially bonded together by an adhesive. A three-layer structure is preferred. In this way, the nanofiber nonwoven fabric can be protected from both sides.
[0034] The nanofiber nonwoven fabric used in the present invention can be manufactured by electrospinning (electrospinning), and the average diameter of the single fibers constituting the nonwoven fabric is preferably 1 to 1000 nm, more preferably 10 to 900 nm, and further preferably 50 to 800 nm. The thickness of the nanofiber nonwoven fabric layer is preferably 0.1 to 100 μm, more preferably 1 to 90 μm, and further preferably 5 to 80 μm. The mass per unit area is preferably 1 to 50 g / m 2 , more preferably 2 to 40 g / m 2 , more preferably 3 to 30 g / m 2 .
[0035] The surface fabric and / or back fabric can be woven or knitted. Knitted fabrics include warp knitting, circular knitting, weft knitting, etc. Fabrics include plain weave, twill weave, satin weave and other variations. Warp knitting or knitted fabrics are preferred. They make it easy for sweat (humid sweat: gas) from the body side to be dissipated to the outside air side through the gaps in the knitted tissue. The preferred mass of the surface fabric is 10 to 150 g / m 2 , more preferably 20 to 140 g / m 2 , more preferably 30 to 130 g / m 2 The preferred weight of the back fabric is 10 to 150 g / m 2 , more preferably 2 to 150 g / m 2 , more preferably 3 to 100 g / m 2 .
[0036] The surface fabric is preferably subjected to a water-repellent treatment in advance. The thickness of the moisture-permeable waterproof laminated fabric of the present invention is preferably 0.15 to 1.0 mm. In addition, the mass of the moisture-permeable waterproof laminated fabric of the present invention is preferably 50 to 200 g / m 2 , more preferably 70 to 160 g / m 2 , more preferably 80 to 140 g / m 2 This will reduce weight.
[0037] Regarding the partial bonding between the surface grey fabric and the nanofiber nonwoven fabric using an adhesive, the ratio of the thickness of the adhesive layer to the thickness of the nanofiber nonwoven fabric layer (impregnation rate) is preferably less than 80%, more preferably 20-80%, and further preferably 25-80%. In this way, the adhesive will not seep through the nanofiber nonwoven fabric or the surface grey fabric to the back and surface, resulting in good quality.
[0038] In addition, the partial lamination is preferably 10 to 80% in terms of area ratio, more preferably 20 to 70%, and further preferably 30 to 60%. As a result, sweat (humid sweat: gas) from the body side can diffuse to the outside air side through the gaps between the yarns or knitted structures of the surface grey fabric layer or the gaps in the nanofiber nonwoven fabric layer, so that even under the action of rainwater and sweat during wearing, the breathability and moisture permeability of the moisture permeable membrane can continue to be exerted.
[0039] Here, the area ratio refers to the ratio of the projected area of the adhesive on the nanofiber nonwoven fabric layer to the sum of the apparent fiber surface area and the void area between nanofibers when the nanofiber nonwoven fabric is viewed from above.
[0040] The coating amount of the adhesive is preferably 2 to 20 g / m 2 , more preferably 3 to 15 g / m 2 , more preferably 4 to 12 g / m 2 As a result, the bonding strength between the nanofiber nonwoven fabric and the surface fabric is high, and no peeling occurs during actual use. The gaps between the fibers of the nanofiber nonwoven fabric can be maintained, and high moisture permeability or air permeability can be maintained, thereby maintaining a good hand feel.
[0041] Regarding the adhesive, it is preferred that the adhesive is impregnated and bonded in a manner that wraps the circumferential direction of the nanofibers in contact with the bonding surface between the nanofiber nonwoven fabric and the grey fabric layer. Since the adhesive is attached in a manner that wraps the fibers of the nanofiber nonwoven fabric, the bonding area between the nanofibers and the adhesive becomes larger and the bonding strength becomes higher. The same is true in the bonding with the waterproof processing layer of the nanofiber nonwoven fabric, because the nanofibers that have been waterproofed are also covered with the adhesive, so the falling off of the waterproof agent on the surface of the nanofiber nonwoven fabric can be suppressed, and it is not easy to cause a decrease in water pressure resistance due to washing.
[0042] Regarding the ratio of the thickness of the adhesive layer in the partial bonding formed by the adhesive of the back fabric and the nanofiber nonwoven fabric, the ratio of the thickness of the adhesive layer to the thickness of the nanofiber nonwoven fabric layer (impregnation rate) is preferably 80% or less, more preferably 20-80%, and further preferably 25-80%. In this way, the adhesive will not penetrate the nanofiber nonwoven fabric or the back fabric and seep out to the back and surface, resulting in good quality. In addition, the partial bonding is preferably 10-80% in terms of area ratio, more preferably 20-70%, and further preferably 30-60%. Thus, sufficient bonding strength can be obtained, the adhesive will not fill the gaps of the nanofiber nonwoven fabric, and a high moisture permeability and air permeability can be maintained, and a good feel can be maintained.
[0043] Regarding the partially bonded portion formed by the adhesive between the surface grey cloth and the nanofiber nonwoven fabric, and the partially bonded portion formed by the adhesive between the back grey cloth and the nanofiber nonwoven fabric, it is preferred that the adhesive is impregnated 20 to 50% in the thickness direction of the nanofiber layer. In this way, sufficient bonding strength can be obtained, high moisture permeability and air permeability can be maintained, and a good hand feel can be maintained. The adhesive is preferably impregnated and bonded in a manner that wraps the circumferential direction of the nanofiber on the surface opposite to the waterproofing of the nanofiber nonwoven fabric. Since the adhesive is attached in a manner that wraps the fibers of the nanofiber nonwoven fabric, the bonding area between the nanofiber and the adhesive becomes larger, so a good bonding strength can be obtained.
[0044] The adhesive may be polyurethane, polyester, polyamide, acrylic, silicone, inorganic, etc., without particular limitation, and preferably has excellent compatibility with the nanofiber nonwoven fabric. For example, when polyurethane is used as the nanofiber, a polyurethane adhesive is preferably used. In addition, when a moisture-curing polyurethane adhesive is used, not only can it be used at low temperatures and thus can be bonded without destroying the structure of the nanofiber nonwoven fabric, but also because it can be bonded without using a solvent, the environmental load is also less, and therefore it is more preferred. The coating amount of the adhesive is preferably 2 to 20 g / m 2 , more preferably 3 to 15 g / m 2 , more preferably 4 to 12 g / m 2 As a result, the high bonding strength between the nanofiber nonwoven fabric and the surface fabric can be maintained, and peeling will not occur during actual use. The moisture permeability and air permeability can be maintained, and a good hand feel can be maintained.
[0045] The air permeability resistance value of the moisture-permeable waterproof laminated fabric in a state where liquid water is 30 to 80% wet is preferably 0 to 277.5 kPa·s / m, and more preferably 55 to 277.5 kPa·s / m. As a result, the air permeability resistance when wet can be maintained at a low level, the moisture permeability and water pressure resistance during wearing can be prevented from decreasing, and a comfortable internal environment of the clothing can be maintained during wearing. In addition, as a pre-test treatment, the moisture-permeable waterproof laminated fabric is immersed in water for 60 seconds and then hung to dry for 30 seconds. At the beginning of the measurement, the measurement is performed after confirming that 30 to 80% of liquid water (wet) is retained relative to 100% of the mass of the moisture-permeable waterproof laminated fabric. In addition, if the moisture-permeable waterproof laminated fabric is in a state where 30 to 80% of liquid water (wet) is retained relative to 100% of its mass, a certain air permeability resistance value is displayed.
[0046] The moisture permeability of the moisture-permeable waterproof laminated fabric in a dry state according to JIS L1099:2012A-1 method is preferably 5000 to 20000 g / m 2 24h, more preferably 7000 to 18000 g / m 2·24h, more preferably 9000~15000g / m 2 In addition, the moisture permeability obtained based on JIS L1099:2012B-1 method is preferably 10000 to 100000 g / m 2 24h, more preferably 20000 to 90000 g / m 2 24h, more preferably 30000 to 80000 g / m 2 ·24h. In addition, the water pressure resistance obtained based on JIS L1092:2009 is preferably 7000mm~30000mm, more preferably 8500mm~30000mm, and further preferably 10000mm~30000mm. The water pressure resistance after 20 washing treatments using the JIS L 1930:2014C4M method is preferably 5000~25000mm, more preferably 7000~25000mm, and further preferably 8000~25000mm. The absolute humidity in the space obtained based on the original method is preferably 10~17g / m 3 Furthermore, the air permeability obtained based on the Frazier method of JIS L1096:2010 is preferably 0.01 to 2 cc / m 2 · seconds, more preferably 0.05 to 1.5 cc / m 2 · seconds, more preferably 0.1 to 1 cc / m 2 · seconds. This allows the inner environment of the clothing to be maintained to be comfortable when worn.
[0047] The method for manufacturing the moisture-permeable waterproof laminated fabric of the present invention is to impart a waterproof agent to the surface fabric side of the nanofiber nonwoven fabric and fix it to form a waterproof layer, and partially bond the waterproof layer side of the nanofiber nonwoven fabric to the surface fabric using an adhesive, or after partially bonding the nanofiber nonwoven fabric to the surface fabric, impart a waterproof agent to the non-contact surface of the nanofiber nonwoven fabric and fix it. Alternatively, after partially bonding the nanofiber nonwoven fabric to the surface fabric and the back fabric, impart a waterproof agent and fix it by a pad and drying method. In this case, the waterproof agent is also applied to the surface of the nanofiber nonwoven fabric through the gaps between the fibers or tissues of the surface fabric and the back fabric.
[0048] Regarding the waterproof layer, it is preferred that at least one side of the nanofiber nonwoven fabric layer is waterproofed with a non-fluorine waterproofing agent. The types of non-fluorine waterproofing agents can use polyurethane, hydrocarbon, silicone, acrylic, etc. Although the previous fluorine-based waterproofing agents are excellent in water resistance and durability, they have a large environmental load and need to be restricted in use, so non-fluorine waterproofing agents are preferably used. Furthermore, it is more preferred to use a non-fluorine-based waterproofing agent with high affinity for nanofiber nonwoven fabrics. For example, in the case where polyurethane fibers are used in nanofiber nonwoven fabrics, polyurethane-based non-fluorine waterproofing agents can be used. Alkyl carbamate-based non-fluorine waterproofing agents are more preferably used. The moisture-permeable waterproof fabric using a fluorine-based waterproofing agent in the past or the moisture-permeable waterproofing laminated fabric using a polytetrafluoroethylene (PTFE) membrane has affinity with the hydrophobic group of the detergent after washing, so the air permeability is reduced. In the case of using an alkyl polyurethane-based non-fluorine waterproofing agent, the affinity with the polyurethane nanofiber nonwoven fabric is high, and the waterproofing agent is easily fixed on the surface of the nanofiber, which can effectively inhibit the decrease in water pressure resistance caused by washing.
[0049] The coating amount of the water repellent agent to the nanofiber nonwoven fabric is preferably 2 to 10% owf (on the weight of fiber). Within the above range, the water repellent agent will not clog the pores of the nanofiber nonwoven fabric and can prevent water from entering.
[0050] Regarding the partial lamination of the waterproof layer side of the nanofiber nonwoven fabric with the surface fabric or the back fabric, it is preferred that an adhesive is partially applied to the surface fabric or the back fabric, and the nanofiber nonwoven fabric is laminated with the waterproof layer side. In addition, the same is true for the bonding of the non-waterproof layer side of the nanofiber nonwoven fabric with the surface fabric or the back fabric, and it is preferred that a waterproof agent is partially applied to the surface fabric or the back fabric, and the nanofiber nonwoven fabric is laminated with the non-waterproof layer side.
[0051] A preferred production method of the present invention is as follows.
[0052] Method A: 3-layer structure, back fabric and nanofiber nonwoven fabric are laminated to form a waterproof layer
[0053] (1) Bonding of back fabric and nanofiber nonwoven fabric
[0054] An adhesive is partially applied to one side of the back fabric to partially bond the back fabric to the nanofiber nonwoven fabric.
[0055] (2) Formation of waterproof layer of nanofiber nonwoven fabric
[0056] Next, a water-repellent agent is applied to the nanofiber nonwoven fabric, and the fabric is aged and fixed to form a water-repellent layer.
[0057] (3) Bonding of surface fabric and nanofiber nonwoven fabric
[0058] Next, an adhesive is partially applied to one side of the surface grey fabric, and the surface grey fabric and the nanofiber nonwoven fabric are partially bonded. In addition, the surface grey fabric is preferably waterproofed in advance, but it can also be waterproofed after bonding. Thus, it is possible to prevent the surface grey fabric from being wetted by rainwater. The grey fabric used in the surface grey fabric can be a fabric or a woven fabric. In addition, the fibers used can be natural fibers such as cotton, linen, silk, wool, etc. in addition to synthetic fibers such as polyester, nylon, polypropylene, acrylonitrile fiber, polyurethane, etc., and can also be mixed fibers, blended, interwoven, and interwoven.
[0059] Method B: 3-layer structure, 3 layers stacked and then padding for waterproofing (padding water-repellent treatment)
[0060] (1) Bonding of back fabric and nanofiber nonwoven fabric
[0061] (2) Formation of a waterproof layer on the nanofiber nonwoven fabric: Formation of a waterproof layer on the surface of the nanofiber nonwoven fabric
[0062] (3) Bonding of back fabric and nanofiber nonwoven fabric
[0063] (4) Waterproofing of laminated fabrics
[0064] Method C: 3-layer structure, the waterproofing order of the surface base fabric of Method A is different
[0065] (1) Bonding of back fabric and nanofiber nonwoven fabric
[0066] (2) Formation of a waterproof layer on the nanofiber nonwoven fabric: Formation of a waterproof layer on the surface of the nanofiber nonwoven fabric
[0067] (3) Lamination of waterproof surface fabric and nanofiber nonwoven fabric
[0068] Method D: 3-layer structure, lamination starts from the front side
[0069] (1) Bonding of surface fabric and nanofiber nonwoven fabric
[0070] (2) Formation of waterproof layer of nanofiber nonwoven fabric
[0071] (3) Bonding of back fabric and nanofiber nonwoven fabric
[0072] (4) Waterproof processing of surface fabric
[0073] Method E: 3-layer structure, lamination starts from the surface side, and the liner is waterproof after lamination of 3 layers
[0074] (1) Bonding of surface fabric and nanofiber nonwoven fabric
[0075] (2) Bonding of back fabric and nanofiber nonwoven fabric
[0076] (3) Waterproofing of laminated fabrics
[0077] Method F: 3-layer structure, lamination starts from the surface side, the surface fabric is waterproof first
[0078] (1) Lamination of waterproof surface fabric and nanofiber nonwoven fabric
[0079] (2) Formation of waterproof layer of nanofiber nonwoven fabric
[0080] (3) Bonding of back fabric and nanofiber nonwoven fabric
[0081] (4) Waterproof processing of surface fabric
[0082] G method: double layer structure, no backing fabric
[0083] (1) Formation of a waterproof layer of nanofiber nonwoven fabric on release paper
[0084] (2) Bonding of surface fabric and nanofiber nonwoven fabric
[0085] (3) Waterproof processing of surface fabric
[0086] Method H: Double-layer structure, the surface fabric is waterproof first
[0087] (1) Formation of a waterproof layer of nanofiber nonwoven fabric on release paper
[0088] (2) Lamination of waterproof surface fabric and nanofiber nonwoven fabric
[0089] Method I: 2.5-layer structure
[0090] (1) Formation of a waterproof layer of nanofiber nonwoven fabric on release paper
[0091] (2) Bonding of surface fabric and nanofiber nonwoven fabric
[0092] (3) Waterproof processing of surface fabric
[0093] (4) Resin processing on the back of nanofiber nonwoven fabric
[0094] J method: 2.5-layer structure, the surface fabric is first waterproof
[0095] (1) Formation of a waterproof layer of nanofiber nonwoven fabric on release paper
[0096] (2) Lamination of waterproof surface fabric and nanofiber nonwoven fabric
[0097] (3) Resin processing on the back of nanofiber nonwoven fabric
[0098] The manufacture of the nanofiber nonwoven fabric used in the present invention has the following methods: melt-blowing method in which molten polymer is blown with hot air to obtain nano-sized fibers and composite melt spinning method in which the sea component of the composite silk of the sea-island structure is dissolved and obtained, but in order to easily control and stably manufacture nanofibers, it is preferably spun and stacked by electrostatic spinning method. The material used to manufacture the nanofiber nonwoven fabric can use polymer materials such as polyurethane, polyester, nylon, polyethylene terephthalate, recycled polyester, polylactic acid, polyacrylonitrile, polyvinylidene fluoride, cross-linked polyvinyl alcohol, but from the viewpoint of flexibility and stretchability, thermoplastic polyurethane is preferably used. As thermoplastic polyurethane, polyester polyurethane can be listed: for example, the trade name "Elastollan, ET680-15MS" of BASF company, polyether polyurethane: for example, the trade name "Elastollan, ET385" of BASF company, etc. The solvent for dissolving the nanofiber raw material is not particularly limited, and the solvent of the polymer material suitable for dissolving the nanofiber raw material can be selected. When manufacturing nanofibers, additives such as heat storage agents, antibacterial agents, antibacterial agents, waterproofing agents, antistatic agents, etc. can be used together with polymer materials for spinning. The average fiber diameter of the nanofibers is preferably 1nm to 1000nm, more preferably 10nm to 900nm, and further preferably 50nm to 800nm. The thickness of the nanofiber nonwoven fabric layer is preferably 0.1μm to 100μm, more preferably 1μm to 90μm, and further preferably 5μm to 80μm. In addition, the mass per unit area of the nanofiber nonwoven fabric layer is preferably 1g / m 2 ~50g / m 2 , more preferably 2g / m 2 ~40g / m 2 , more preferably 3g / m 2 ~30g / m 2 The fibers constituting the nanofiber nonwoven fabric layer are preferably fibers obtained by electrospinning (electrospinning).
[0099] As the waterproofing agent used in the waterproofing of at least one side of the nanofiber nonwoven fabric, it can be the so-called C6 waterproofing agent or the C0 waterproofing agent. From the perspective of environmental protection in recent years, it is preferred to use the C0 waterproofing agent. In addition, the main components of the waterproofing agent are silicone, polyurethane, acrylic, hydrocarbon, etc., and any of them can be used. As a method for direct waterproofing of at least one side of the nanofiber nonwoven fabric, padding treatment, coating using a roller screen, a flat screen, and a sprayer can be listed, and any one of them can be used. In order to cover the surface layer of the nanofiber nonwoven fabric 100% with a waterproofing agent, padding treatment is preferred, and in order to set it to be partially waterproof, processing using a roller screen or a flat screen and a sprayer is preferred. In addition, even if waterproofing is performed after laminating with the surface grey fabric or the back grey fabric, the nanofiber nonwoven fabric surface can also be waterproofed. For example, in the case of waterproofing after laminating the surface grey fabric and the nanofiber nonwoven fabric, the waterproofing agent will also reach the surface grey fabric layer side of the nanofiber nonwoven fabric from the gaps between the fibers of the surface grey fabric or the gaps in the organization. Even after the back grey fabric and the nanofiber nonwoven fabric are bonded, in the case of waterproofing from the back grey fabric side, the waterproofing agent will also reach the back grey fabric layer side of the nanofiber nonwoven fabric from the gaps between the fibers of the back grey fabric or the gaps of the organization. In the case of using a mesh material as the back grey fabric, the amount of the waterproofing agent that passes through the back grey fabric and reaches the back grey fabric layer of the nanofiber nonwoven fabric becomes more, and the waterproofing agent can reach the surface grey fabric layer side of the nanofiber nonwoven fabric. The same is true in the waterproofing after bonding the surface grey fabric and the back grey fabric to the nanofiber nonwoven fabric. As a method for waterproofing after bonding the surface grey fabric or the back grey fabric, or both of them to the nanofiber nonwoven fabric, pad treatment, coating using a roller screen, a flat screen, a sprayer, etc. can be cited, and any one of them can be used.
[0100] In the surface fabric, the air permeability (JIS L 1096) is preferably 5cc / cm 2 As a result, the waterproofing agent can effectively penetrate from the gaps between the fibers of the surface grey fabric and the gaps in the tissue to reach the surface of the nanofiber nonwoven fabric layer, and the waterproofing agent is applied to the surface of the nanofiber nonwoven fabric layer.
[0101] When the back grey fabric and the nanofiber nonwoven fabric are bonded together and waterproofing is performed from the back grey fabric side, if the nanofiber nonwoven fabric is thermoplastic polyurethane and the main components of the waterproofing agent are silicone-based and urethane-based, the nanofiber nonwoven fabric has a high affinity for the waterproofing agent and can reach the surface grey fabric layer side of the nanofiber nonwoven fabric more efficiently.
[0102] When the nanofiber nonwoven fabric is joined to the surface grey fabric, the nanofibers can be directly stacked on the grey fabric, or the nanofibers spun and stacked on the release paper can be joined to the grey fabric through an adhesive. From the viewpoint of performance stability, it is preferred to spin and stack on the release paper and join with an adhesive. The adhesive used in the joining of the nanofiber nonwoven fabric to the surface grey fabric can be a polyurethane system, an epoxy system, a melamine system, a nylon system, etc., in addition, it can also be a single liquid type, a two-liquid type, and other adhesives can also be used. In the bonding method of the nanofiber nonwoven fabric to the surface grey fabric, the adhesive can be applied to the surface grey fabric using a knife coater, a roll coater, a rod coater, a spray coating and other processing methods. If the adhesive is applied in a manner that completely covers the surface of the nanofiber nonwoven fabric, in addition to the hardening of the feel, it will also hinder the moisture permeability and air permeability, so it is preferred to partially bond. As long as the nanofiber nonwoven fabric and the surface fabric can be bonded by partially applying the adhesive, any bonding method such as a knife coater, a roll coater, a rod coater, or a spray coating may be used.
[0103] The back side of the moisture-permeable waterproof laminate can be used without processing, or can be processed with resin, or can be bonded with another layer of grey cloth. When used without processing, it is preferable to use the laminate in a way that the back side of the laminate is not visible due to concerns about the destruction of the nanofibers, such as using it as a fabric for a down jacket or a cotton jacket. In addition, in the case of resin processing, resins such as polyurethane resin, acrylic resin, and nylon resin can be used. In addition, as a method of implementing resin processing, a gravure roller can be used to apply a partial pattern, or a knife coater can be used to apply the resin on the entire surface.
[0104] When a layer of grey fabric is bonded to the back side of the moisture-permeable waterproof laminated fabric, the back grey fabric may be a warp knitted fabric, a cylindrical knitted fabric, or a woven fabric. In addition, the fibers used may be synthetic fibers such as polyester, nylon, polypropylene, acrylonitrile fiber, and polyurethane, or natural fibers such as cotton, linen, silk, and wool. In addition, they may be mixed, blended, interwoven, or interwoven. The back grey fabric is preferably a half-tricot fabric using a nylon multifilament warp pile-warp plain weave.
[0105] The grey fabric used in the surface grey fabric can be a woven fabric or a knitted fabric. In addition, the fibers used can be natural fibers such as cotton, linen, silk, wool, etc. in addition to synthetic fibers such as polyester, nylon, polypropylene, acrylonitrile fiber, polyurethane, etc., and can also be mixed fibers, blended, interwoven, or interwoven. Among them, the surface grey fabric is preferably a warp-pile warp plain warp knitted fabric using polyester (PET) multifilament.
[0106] In the following drawings described using the following drawings, the same symbols represent the same components. Figure 1 This is a schematic cross-sectional view of a two-layer moisture-permeable waterproof laminated fabric according to an embodiment of the present invention. In the moisture-permeable waterproof laminated fabric 1, a nanofiber nonwoven fabric layer 3 is laminated on one side of a surface grey fabric layer 2, and the surface grey fabric layer 2 and the nanofiber nonwoven fabric layer 3 are bonded together by a partial bonding portion 4. In addition, a waterproof layer 5 is formed on the surface of the nanofiber nonwoven fabric layer 3 on the side of the surface grey fabric layer 2.
[0107] Figure 2 Schematic cross-sectional view of a 2.5-layer moisture-permeable waterproof laminate fabric 6 according to one embodiment of the present invention. Figure 1 The difference is that a printed layer 7 is formed on the back side of the nanofiber nonwoven fabric layer 3 .
[0108] Figure 3 Schematic cross-sectional view of a moisture-permeable waterproof laminated fabric 9 having a three-layer structure according to one embodiment of the present invention. Figure 1 The difference is that a back surface fabric layer 10 is formed on the back surface of the nanofiber nonwoven fabric layer 3 , and the nanofiber nonwoven fabric layer 3 and the back surface fabric layer 10 are bonded together via a partial bonding portion 8 .
[0109] Figure 4A -E is a schematic cross-sectional process diagram showing a method for producing a three-layer moisture-permeable waterproof laminated fabric according to one embodiment of the present invention. Figure 4A As shown, an adhesive is partially applied to one side of the back fabric layer 10, and the back fabric 10 and the nanofiber nonwoven fabric 3 are bonded together through the partial bonding portion 8. Figure 4B The following is the status of Figure 4C As shown in FIG. 1 , a waterproofing agent is partially applied to the nanofiber nonwoven fabric layer 3, aged and fixed to form a waterproof layer 5. Next, as shown in FIG. Figure 4D As shown, an adhesive is partially applied to one side of the surface fabric layer 2, and the surface fabric layer 2 and the nanofiber nonwoven fabric layer 3 are bonded together through the partial bonding portion 4. Figure 4E The moisture-permeable waterproof laminated fabric 9 was obtained.
[0110] Figure 5 It is a schematic cross-sectional view showing the bonding state of the nanofiber nonwoven fabric layer and the surface grey fabric layer according to one embodiment of the present invention. In the partial bonding portion 11, there is an adhesive 13 between the fibers 12 of the surface grey fabric layer and the fibers 14 of the nanofiber nonwoven fabric layer, and the adhesive 13 is impregnated in a manner of wrapping the fibers 12 of the surface grey fabric layer and the fibers 14 of the nanofiber nonwoven fabric layer. This can improve the bonding strength. The adhesive is preferably impregnated and bonded in a manner of wrapping the circumferential direction of the nanofibers on the waterproof processing layer side of the nanofiber nonwoven fabric. Since the adhesive is attached in a manner of wrapping the fibers of the nanofiber nonwoven fabric, the bonding area between the nanofibers and the adhesive becomes larger, thereby being able to obtain good bonding strength.
[0111] Figure 6 This is a plan view photograph (scanning electron microscope: SEM, magnification 10000 times) of a nanofiber nonwoven fabric according to one embodiment of the present invention. Figure 7 This is a plan view photograph (SEM, 2000-fold magnification) of a nanofiber nonwoven fabric according to one embodiment of the present invention.
[0112] Example
[0113] The following examples are used to further illustrate the present invention. In addition, the present invention should not be construed as being limited to the following examples.
[0114] The evaluation method is as follows.
[0115] <Mass per unit area>
[0116] The measurement was carried out according to JIS L1096:2010A method.
[0117] <Water pressure resistance>
[0118] The measurement was carried out according to JIS L1092:2009B method.
[0119] <Moisture Permeability>
[0120] The following three methods were used for determination.
[0121] JIS L1099:2012A-1 method
[0122] JIS L1099:2012B-1 method
[0123] Original method
[0124] like Fig. 8A -B moisture permeability measuring device 15, a glass petri dish 17 with a diameter of 6.4 cm is set on a hot plate 16 controlled at 35°C. About 15g of water is added to the petri dish 17. A polypropylene BOX (box) 18 (length 15cm, width 15cm, height 3.5cm) is set in a manner to cover the petri dish 17 and the hot plate 16. A 10cm×10cm opening is provided on the upper part of the BOX 18, and a grey cloth 20 (cut into a size of 15cm×15cm) is attached in a manner to cover the opening. A wind 21 of 0.3m / sec is blown from above the grey cloth 20 as indicated by the arrow. A temperature and humidity sensor 19 (Hygrochrons, KN Laboratories Co., Ltd.) is attached to the inner wall of the BOX 18 to measure the temperature and relative humidity in the space formed by the hot plate 16, the BOX 18 and the grey cloth 20. Based on the measured temperature and relative humidity, the absolute humidity is calculated by the following formula. The measurement was performed in a room with a temperature and humidity controlled to 20°C and a relative humidity of 65%RH.
[0125] Absolute humidity (g / m 3 )=217×6.1078×10 (7.5×T / (T+237.3)) / (T+273.15) ×RH / 100
[0126] Where, T: temperature (℃), RH: relative humidity (%)
[0127] In addition, this test method is implemented under two conditions: dry state and wet state. In the dry state, the grey cloth is placed as a test sample in a room controlled at a temperature of 20°C and a relative humidity of 65%RH for more than 24 hours, and the above test is implemented under the state of temperature and humidity control. In the wet state, the grey cloth is immersed in ion exchange water for 1 hour, and then hung to dry for 1 minute to remove the water droplets on the grey cloth.
[0128] <Breathable resistance>
[0129] The measurement was performed using an air permeability resistance tester KS-F8 (manufactured by Kato Tech Co., Ltd.) The measurement was performed by releasing and sucking air into the air, detecting the pressure during the release and suction, and calculating the air permeability resistance R.
[0130] Air permeability: 0.4cc / cm 2 / sec(Constant air flow rate mode)
[0131] Ventilation hole area: 2πcm 2
[0132] The air permeability resistance when dry is measured at a temperature of 20°C and a relative humidity of 65% RH when the grey cloth is dried. The air permeability resistance when wet is measured in a state where the release and suction directions of the air are parallel to the ground, relative to 100% of the mass of the grey cloth, when it is wet with 30 to 80% of water. The temperature and humidity are the same as above. As a pretreatment for the wet test, the moisture-permeable waterproof layer laminate is immersed in ion exchange water for 60 seconds and then hung to dry for 30 seconds. At the beginning of the measurement, the measurement is performed after confirming that 30 to 80% of liquid water is retained relative to 100% of the mass of the moisture-permeable waterproof layer laminate. In addition, if 30 to 80% of liquid water (wet) is retained relative to 100% of the mass of the moisture-permeable waterproof layer laminate, it can also be confirmed that a certain air permeability resistance value is displayed. The measurement method is as follows.
[0133] (1) Immerse the grey fabric in a water tank in a state in which it is perpendicular to the ground, take out the sample, and place the grey fabric on the testing machine.
[0134] (2) Measured according to the method in the KES test manual.
[0135] <Breathability>
[0136] The air permeability of the grey fabric was measured according to JIS L1096:2010 (Frazier method).
[0137] (Example 1)
[0138] (1) Surface fabric
[0139] Polyester multifilament with 22 decitex and 24 filaments was knitted using a No. 40 warp knitting machine (Tricot warp knitting machine). Then, it was refined, pre-shaped, dyed, waterproofed, and heat-set to be used as the surface fabric. The mass of the surface fabric was 73 g / m 2 .
[0140] (2) Back fabric
[0141] 22 decitex, 12 filament nylon yarn was used to weave a half-tricot weave using a tricot knitting machine. Then, dyeing and finishing were performed to obtain the back fabric. The mass of the back fabric was 22 g / m 2 .
[0142] (3) Nanofiber nonwoven fabric
[0143] Nanofiber nonwoven fabrics are prepared by electrospinning. The material of the nanofibers is thermoplastic polyurethane (polyester polyurethane), and the solvent is an organic solvent that can dissolve polyurethane and a polar solvent suitable for electrospinning (a mixed solvent of dimethylformamide and methyl ethyl ketone). The average fiber diameter of the single fiber that constitutes the polyurethane nanofiber nonwoven fabric is 250nm. The film thickness of the nonwoven fabric is 19μm, and the mass per unit area is 7.5g / m 2 .
[0144] (4) Bonding of back fabric and nanofiber nonwoven fabric
[0145] A polyamide hot melt adhesive was applied in dots on the back fabric, and the nanofiber nonwoven fabric was overlapped on the surface coated with the adhesive. In this state, the fabric was passed through a hot roller at a temperature of 110°C for pressure bonding and then rolled up. When the entire area was set to 100%, the bonding area between the back fabric and the nanofiber nonwoven fabric was 40%. In addition, the impregnation rate of the adhesive in the thickness direction was 30%.
[0146] (5) Waterproofing of the surface of nanofiber nonwoven fabric
[0147] After bonding the surface grey fabric to the nanofiber nonwoven fabric, the surface of the nanofiber nonwoven fabric is waterproofed. As a waterproofing agent, a 100-fold diluted solution of a non-fluorine-based waterproofing agent (ON Water Repellent NF, manufactured by NAGASE-OG COLORS & CHEMICALS) with alkyl carbamate as the main component is prepared, and a sprayer is used to apply the waterproofing agent to the surface of the nanofiber nonwoven fabric surface layer to reach 4% owf (on the weight of fiber). After applying the waterproofing agent, dry it at 110°C for 1 minute. The thickness of the waterproof layer formed on the surface of the nanofiber nonwoven fabric is 30% from the surface of the nanofiber nonwoven fabric. When the entire area is set to 100%, the coating area ratio of the waterproofing agent is 80%.
[0148] (6) Bonding of surface fabric
[0149] The nanofiber nonwoven fabric with a waterproof surface was bonded to the surface fabric. A moisture-curable urethane adhesive was used as an adhesive and the adhesive was applied with a sprayer to a density of 10 g / m 2 After coating, the adhesive was fixed by passing through a heating roller at 110°C and 20 m / min to obtain a laminated fabric. When the entire area is set to 100%, the bonding area between the surface fabric and the nanofiber nonwoven fabric is 40%. In addition, the impregnation rate of the adhesive in the thickness direction is 30%.
[0150] The thickness of the moisture-permeable waterproof laminated fabric thus obtained was 0.44 mm in a static state.
[0151] (Example 2)
[0152] 22 decitex, 24 filament polyester yarn was used as the surface fabric, and a gauge warp knitting machine was used to knit a warp knitted mesh fabric. Then, it was refined, pre-shaped, dyed, waterproofed, and heat-set, and used as the surface fabric. The mass of the surface fabric was 53 g / m 2 The same operation as in Example 1 was carried out except for the above.
[0153] The thickness of the moisture-permeable waterproof laminated fabric thus obtained was 0.50 mm in a static state.
[0154] (Example 3)
[0155] The average fiber diameter of the polyurethane nanofibers was set to 250 nm, the film thickness of the nanofiber nonwoven fabric layer was set to 12 μm, and the mass of the nanofiber nonwoven fabric layer was set to 6 g / m 2 . Spray a moisture-curing polyurethane hot melt adhesive onto the back fabric to a concentration of 10 g / m 2The nanofiber nonwoven fabric was overlapped on the surface coated with the adhesive, and in this state, it was pressed and bonded by a hot roller and then rolled up. The hot pressing temperature was 110° C. and the winding speed was 20 m / min. Other than that, the processing was carried out in the same manner as in Example 1.
[0156] In the bonding between the back fabric and the nanofiber nonwoven fabric, the bonding area was 45% when the entire area was set as 100%. In addition, the impregnation rate of the adhesive in the thickness direction was 40%.
[0157] The thickness of the waterproof layer of the nanofiber nonwoven fabric surface layer was 40% from the nanofiber nonwoven fabric surface layer, and when the entire area was set to 100%, the coating area ratio of the waterproof agent was 85%.
[0158] When the entire area is defined as 100%, the bonding area between the surface fabric and the waterproof nanofiber nonwoven fabric is 45%, and the impregnation rate of the adhesive in the thickness direction is 40%.
[0159] The thickness of the moisture-permeable waterproof laminated fabric thus obtained was 0.52 mm in a static state.
[0160] (Example 4)
[0161] In the bonding process between the back fabric and the nanofiber nonwoven fabric, a moisture-curable polyurethane hot melt adhesive is sprayed on the back fabric to a density of 7 g / m 2 The nanofiber nonwoven fabric was overlapped on the surface coated with the adhesive, and in this state, it was pressed and bonded by a hot roller and then rolled up. The hot pressing temperature was 110° C. and the winding speed was 20 m / min. The same operation as in Example 3 was carried out except for this.
[0162] The thickness of the moisture-permeable waterproof laminated fabric thus obtained was 0.52 mm in a static state.
[0163] (Example 5)
[0164] (1) Surface fabric
[0165] 44 decitex, 36 filament nylon multifilament was used to make the density reach 150 strands / inch in the longitudinal direction and 100 strands / inch in the transverse direction, and it was woven, refined, pre-shaped, dyed, waterproofed, and heat-set to be used as the surface fabric. The mass of the surface fabric is 43g / m 2 .
[0166] (2) Back fabric
[0167] The back fabric described in Example 1 was used.
[0168] (3) Nanofiber nonwoven fabric
[0169] The nanofiber nonwoven fabric described in Example 3 was used.
[0170] (4) Bonding of back fabric and nanofiber nonwoven fabric
[0171] Apply moisture-curing polyurethane hot melt adhesive in dots on the back fabric to a density of 6 g / m 2 The nanofiber nonwoven fabric is overlapped on the surface coated with the adhesive, and is pressure-bonded by a hot roller and then rolled up.
[0172] In the bonding between the back fabric and the nanofiber nonwoven fabric, the bonding area was 55% when the entire area was set as 100%. In addition, the impregnation rate of the adhesive in the thickness direction was 28%.
[0173] (5) Waterproofing of the surface of nanofiber nonwoven fabric
[0174] After bonding the surface grey fabric to the nanofiber nonwoven fabric, the surface of the nanofiber nonwoven fabric is waterproofed. As a waterproofing agent, a 100-fold diluted solution of a non-fluorine-based waterproofing agent (ON Water Repellent NF, made by NAGASE-OG COLORS & CHEMICALS) with alkyl carbamate as the main component is prepared, and a sprayer is used to apply the waterproofing agent to the surface of the nanofiber nonwoven fabric to reach 4% owf (on the weight of fiber). After applying the waterproofing agent, dry it at 110°C for 1 minute. The thickness of the waterproof layer formed on the surface of the nanofiber nonwoven fabric is 30% from the surface layer of the nanofiber nonwoven fabric. When the entire area is set to 100%, the coating area ratio of the waterproofing agent is 80%.
[0175] (6) Bonding of surface fabric
[0176] The surface of the nanofiber nonwoven fabric with waterproof treatment was bonded to the surface fabric. As an adhesive, a moisture-curable polyurethane hot melt adhesive was applied in dots on the surface fabric to a density of 9 g / m 2 The nanofiber nonwoven fabric was overlapped on the surface coated with the adhesive, and in this state, it was pressed and bonded by a hot roller and rolled up to fix the adhesive to obtain a laminated fabric. When the entire area is set to 100%, the bonding area between the surface grey fabric and the nanofiber nonwoven fabric is 60%. In addition, the impregnation rate of the adhesive in the thickness direction is 35%.
[0177] The thickness of the moisture-permeable waterproof laminated fabric thus obtained was 0.37 mm in a static state.
[0178] (Example 6)
[0179] (1) Surface fabric
[0180] The surface fabric described in Example 2 was used.
[0181] (2) Back fabric
[0182] The back fabric described in Example 1 was used.
[0183] (3) Nanofiber nonwoven fabric
[0184] The nanofiber nonwoven fabric described in Example 3 was used.
[0185] (4) Bonding of back fabric and nanofiber nonwoven fabric
[0186] Apply moisture-curing polyurethane hot melt adhesive in dots on the back fabric to a thickness of 12 g / m 2 The nanofiber nonwoven fabric is overlapped on the surface coated with the adhesive, and in this state, it is pressed and bonded by a hot roller and then rolled up.
[0187] In the bonding between the back fabric and the nanofiber nonwoven fabric, the bonding area was 60% when the entire area was 100%. In addition, the impregnation rate of the adhesive in the thickness direction was 40%.
[0188] (5) Bonding of back fabric
[0189] The back fabric was bonded to the surface of the nanofiber nonwoven fabric opposite to the surface fabric bonded to the back fabric. A moisture-curable urethane adhesive was used as the adhesive, and the adhesive was applied in dots with a gravure roller to a density of 10 g / m 2 The adhesive was fixed to obtain a laminated fabric. When the entire area was set as 100%, the bonding area between the back fabric and the nanofiber nonwoven fabric was 35%. In addition, the impregnation rate of the adhesive in the thickness direction was 40%.
[0190] (6) Waterproofing of laminated fabrics
[0191] The laminated fabric produced above was applied with a waterproofing agent by pad and drying method so that the non-fluorine-based waterproofing agent with alkyl carbamate as the main component reached 5% owf. After applying the waterproofing agent, it was dried at 150°C for 90 seconds. The thickness of the waterproof layer formed on the nanofiber nonwoven fabric was 20% on the surface grey fabric layer side and 30% on the back grey fabric layer side. Regarding the coating area ratio of the waterproofing agent, it was 60% on the surface grey fabric layer side and 80% on the back grey fabric layer side.
[0192] The thickness of the moisture-permeable waterproof laminated fabric thus obtained was 0.60 mm in a static state.
[0193] (Example 7)
[0194] (1) Surface fabric
[0195] The surface fabric described in Example 2 was used.
[0196] (2) Back fabric
[0197] The back fabric described in Example 1 was used.
[0198] (3) Nanofiber nonwoven fabric
[0199] The nanofiber nonwoven fabric described in Example 3 was used.
[0200] (4) Bonding of surface fabric and nanofiber nonwoven fabric
[0201] The same procedure as in Example 6 was carried out.
[0202] (5) Bonding of back fabric
[0203] The same procedure as in Example 5 was carried out.
[0204] (6) Waterproofing of the surface of the laminated fabric on the grey fabric side
[0205] For the laminated fabric manufactured as above, a waterproofing agent was applied from the surface grey fabric side by a gravure roller so that the non-fluorine-based waterproofing agent with alkyl carbamate as the main component reached 5% owf. After applying the waterproofing agent, it was dried at 150°C for 90 seconds. The waterproofing agent processed on the surface grey fabric was impregnated into the surface layer of the nanofiber nonwoven fabric, and the thickness of the waterproof layer was 38%. In addition, when the entire area was set to 100%, the coating area ratio of the waterproofing agent was 78%.
[0206] The thickness of the moisture-permeable waterproof laminated fabric thus obtained was 0.61 mm in a static state.
[0207] (Example 8)
[0208] (1) Surface fabric
[0209] The surface fabric described in Example 2 was used.
[0210] (2) Back fabric
[0211] The back fabric described in Example 1 was used.
[0212] (3) Nanofiber nonwoven fabric
[0213] The nanofiber nonwoven fabric described in Example 3 was used.
[0214] (4) Bonding of surface fabric and nanofiber nonwoven fabric
[0215] Apply moisture-curing polyurethane hot melt adhesive in dots on the surface fabric to a density of 12 g / m 2The nanofiber nonwoven fabric is overlapped on the surface coated with the adhesive, and in this state, it is pressed and bonded by a hot roller and then rolled up.
[0216] In the bonding between the surface fabric and the nanofiber nonwoven fabric, the bonding area was 60% when the entire area was set as 100%. In addition, the impregnation rate of the adhesive in the thickness direction was 40%.
[0217] (5) Waterproofing of the back side of nanofiber nonwoven fabric
[0218] After bonding the surface grey fabric to the nanofiber nonwoven fabric, the back grey fabric surface of the nanofiber nonwoven fabric is waterproofed. A waterproofing agent is applied to the back grey fabric side of the nanofiber nonwoven fabric using a gravure roller so that the non-fluorine-based waterproofing agent with alkyl carbamate as the main component as the waterproofing agent reaches 5% owf. After applying the waterproofing agent, it is dried at 150°C for 90 seconds. The thickness of the waterproof layer formed on the surface of the nanofiber nonwoven fabric is 30% from the surface layer of the nanofiber nonwoven fabric. When the entire area is set to 100%, the coating area ratio of the waterproofing agent is 80%.
[0219] (6) Bonding of back fabric
[0220] The back fabric was bonded to the surface of the nanofiber nonwoven fabric opposite to the surface fabric bonded to the back fabric. As the adhesive, a moisture-curing urethane adhesive was used, and the adhesive was applied in dots with a gravure roll to a density of 10 g / m 2 The adhesive was fixed to obtain a laminated fabric. When the entire area was set as 100%, the bonding area between the back fabric and the nanofiber nonwoven fabric was 60%. In addition, the impregnation rate of the adhesive in the thickness direction was 40%.
[0221] (7) Waterproofing of the surface of the laminated fabric on the grey fabric side
[0222] For the laminated fabric manufactured as above, a waterproofing agent is applied from the surface grey fabric side by a gravure roller so that the non-fluorine-based waterproofing agent with alkyl carbamate as the main component reaches 5% owf. After applying the waterproofing agent, it is dried at 150°C for 90 seconds. The waterproofing agent processed on the surface grey fabric is impregnated into the surface layer of the nanofiber nonwoven fabric, and the thickness of the waterproof layer is 30%. In addition, when the entire area is set to 100%, the coating area ratio of the waterproofing agent is 80%.
[0223] The thickness of the moisture-permeable waterproof laminated fabric thus obtained was 0.61 mm in a static state.
[0224] (Comparative Example 1)
[0225] The following commercial product A was tested: the surface fabric was a ripstop fabric made of nylon yarn (fineness 44 decitex, 36 filaments), the back fabric was a tricot warp knitted fabric made of nylon yarn, and a polyurethane nonporous film was used instead of the nanofiber nonwoven fabric.
[0226] (Comparative Example 2)
[0227] The following commercial product B was tested: the surface fabric was a taffeta fabric of nylon yarn (fineness 44 decitex, 36 filaments), a polyurethane nonporous membrane was used instead of the nanofiber nonwoven fabric, and a polyurethane resin was dot-coated instead of the back fabric.
[0228] (Comparative Example 3)
[0229] The following commercial product C was tested: as the surface fabric, a taffeta fabric using nylon multifilaments as warp and weft, a polyurethane nonporous membrane was used instead of the nanofiber nonwoven fabric, and a polyurethane resin was dot-coated instead of the back fabric.
[0230] (Comparative Example 4)
[0231] The following commercial product D was tested: as the surface fabric, it was a taffeta-structured fabric using nylon yarns as warp and weft yarns, and a polytetrafluoroethylene (PTFE) film was used instead of the nanofiber nonwoven fabric.
[0232] (Comparative Example 5)
[0233] The following commercial product E was tested: the surface fabric was a ripstop fabric using nylon yarns as warp and weft yarns, the back fabric was a plain knitted fabric of nylon yarns, and a polytetrafluoroethylene (PTFE) film was used instead of the nanofiber nonwoven fabric.
[0234] (Comparative Example 6)
[0235] The following commercial product F was tested: as the surface fabric, it was a ripstop fabric using nylon yarns as warp and weft yarns, and the back fabric was a plain knitted fabric of polyester yarns. Nanofiber nonwoven fabric was used as a moisture-permeable waterproof membrane, but the surface of the nanofiber nonwoven fabric was not waterproofed.
[0236] (Comparative Example 7)
[0237] The following commercial product G was tested: a plain-knitted fabric of polyester yarn was used as the front and back fabrics, and a polyurethane nonporous film was used instead of the nanofiber nonwoven fabric.
[0238] The above conditions and the obtained results are shown in Table 1 and Table 2.
[0239]
[0240]
[0241] From Tables 1 and 2, it can be confirmed that the moisture-permeable waterproof laminated fabric of the present invention continuously exhibits the air permeability and moisture permeability of the moisture-permeable membrane not only in a dry state but also in rain and sweat during wearing.
[0242] Garments were sewn using the moisture-permeable waterproof laminated fabrics of Examples 1 and 2, and a wearing test was conducted. Comparative Examples 1 and 2 were worn using commercially available garments.
[0243] The conditions of the wearing test are as follows.
[0244] In a test room with a temperature of 20°C and a relative humidity of 65% RH, a temperature and humidity sensor (Hygrochrons, KN Laboratories Co., Ltd.) was used to measure the temperature and relative humidity inside the clothes when running on a treadmill at a speed of 10 km / hr for 30 minutes. Based on the obtained temperature and relative humidity, the absolute humidity was calculated using the following formula.
[0245] Absolute humidity (g / m 3 )=217×6.1078×10( 7.5×T / (T+237.3)) / (T+273.15) ×RH / 100
[0246] Temperature and humidity sensors were attached to four points on the chest, abdomen, back, and waist. The data from the second half of the 10 minutes of running time was used for evaluation, and the average absolute humidity of each part was used for comparison. The results are shown in Table 3.
[0247] The wearing conditions were as follows: the upper garment was a two-way tricot knitted fabric of 86% polyester and 14% polyurethane, and the measurement sample was worn on top of it, and the lower garment was a 100% polyester cloth shorts.
[0248] Table 3
[0249] Example 1 Example 2 Comparative Example 1 Comparative Example 2 <![CDATA[Absolute humidity inside the clothes (g / m 3 )]]> 21.15 21.18 23.59 24.14
[0250] As can be seen from Table 3, the absolute humidity inside the garments of Examples 1 and 2 is lower than that of the garments of Comparative Examples 1 and 2. In addition, even under the effects of rain and sweat during wearing, the garments of Examples 1 and 2 do not feel stuffy inside the garments, and can maintain a comfortable environment inside the garments.
[0251] Industrial Applicability
[0252] The breathable waterproof laminated fabric of the present invention can be applied to clothing materials such as outdoor clothing such as fishing or mountaineering clothing, ski and skateboard clothing, windbreakers, sportswear, golf clothing, tennis clothing, raincoats, casual wear, work clothes, gloves or boots, surface fabrics of down jackets and padded jackets, glove liners or boot liners, and can also be applied to non-clothing materials such as building materials such as wallpaper or roof waterproof sheets.
[0253] Explanation of symbols
[0254] 1, 6, 9 breathable waterproof layer fabric
[0255] 2 Surface fabric layer
[0256] 3 Nanofiber nonwoven fabric layer
[0257] 4, 8, 11 Partial bonding
[0258] 5 Waterproof layer
[0259] 7 Printing layer
[0260] 10 Back fabric layer
[0261] 12 Fibers of the surface fabric layer
[0262] 13 Adhesive
[0263] 14 Fibers of the nanofiber nonwoven layer
[0264] 15 Moisture permeability measuring device
[0265] 16 Hot Plate
[0266] 17. Glass Petri Dish
[0267] 18 Box
[0268] 19 Temperature and humidity sensor
[0269] 20 Grey cloth
[0270] 21 Wind
Claims
1. A moisture-permeable waterproof laminated fabric, characterized in that: It is a breathable and waterproof laminated fabric with a nanofiber nonwoven fabric layer laminated on one side of the surface grey fabric layer. At least one side of the nanofiber nonwoven fabric layer is a waterproof layer, The surface grey fabric layer and the nanofiber nonwoven fabric layer are bonded to each other through a partial bonding portion.
2. The moisture-permeable waterproof laminated fabric according to claim 1, wherein: The waterproof layer is formed on the surface grey fabric layer side of the nanofiber nonwoven fabric layer.
3. The moisture-permeable waterproof laminated fabric according to claim 1 or 2, wherein: A back grey fabric layer is also laminated on the back side of the nanofiber nonwoven fabric layer. The nanofiber nonwoven fabric layer and the back surface fabric layer are bonded to each other via a partial bonding portion.
4. The moisture-permeable waterproof laminated fabric according to any one of claims 1 to 3, wherein When the fiber surface area of the surface of the nanofiber nonwoven fabric subjected to water-repellent treatment is assumed to be 100%, the water-repellent layer has an area ratio of 10 to 100%.
5. The moisture-permeable waterproof laminated fabric according to any one of claims 1 to 4, wherein The partially bonded portion between the front fabric layer and the nanofiber nonwoven fabric layer, or the partially bonded portion between the back fabric layer and the nanofiber nonwoven fabric layer, is in the range of 10 to 80% by area ratio.
6. The moisture-permeable waterproof laminated fabric according to any one of claims 1 to 5, wherein The water-repellent layer is formed by applying a non-fluorine-based water-repellent agent to at least one surface of the nanofiber nonwoven fabric layer.
7. The moisture-permeable waterproof laminated fabric according to any one of claims 1 to 6, wherein The nanofiber nonwoven fabric layer is composed of nanofibers formed of thermoplastic polyurethane and having an average fiber diameter of 1 nm to 1000 nm.
8. The moisture-permeable waterproof laminated fabric according to any one of claims 1 to 7, wherein The moisture-permeable waterproof laminated fabric has an air permeability resistance value of 0 to 277.5 kPa·s / m when wetted with water.
9. The moisture-permeable waterproof laminated fabric according to any one of claims 1 to 8, wherein The moisture permeability of the moisture-permeable waterproof laminated fabric in a dry state according to JIS L1099 A-1 method is 5000 to 20000 g / m 2 ·24h, moisture permeability according to JIS L1099B-1 method is 10000~100000g / m 2 ·24h.
10. The moisture-permeable waterproof laminated fabric according to any one of claims 1 to 9, wherein The moisture-permeable waterproof laminated fabric has a water pressure resistance of 7000 to 30000 mm before washing according to JIS L1099, and a water pressure resistance of 5000 to 25000 mm after washing 20 times.
11. The moisture-permeable waterproof laminated fabric according to any one of claims 1 to 10, wherein The moisture-permeable waterproof laminate has an air permeability of 0.01 to 2 cc / m according to the Frazier method of JIS L1096. 2 ·Second.
12. The moisture-permeable waterproof laminated fabric according to any one of claims 1 to 11, wherein The surface grey cloth is waterproofed.
13. A method for producing a moisture-permeable waterproof laminated fabric, characterized in that: A method for producing a moisture-permeable waterproof layer fabric according to any one of claims 1 to 12, A water-repellent agent is applied to at least one side of the nanofiber nonwoven fabric layer and fixed to form a water-repellent layer. The nanofiber nonwoven fabric layer and the surface grey fabric layer are partially bonded by using an adhesive.
14. A garment using the moisture-permeable waterproof layer fabric according to any one of claims 1 to 12.
Citation Information
Patent Citations
Moisture-permeable waterproof cloth
JP2007136970A
Moisture permeable waterproof cloth
JP2008213391A
Laminated cloth and method for manufacturing the same
JP2010030289A
Moisture-permeable and water-proof fabric and process for production of same
JP2010255132A
Flame-retardant PVC (polyvinyl chloride) coated fabric
CN213564829U